On Self Codes: a Case Study within Mathematics and Performance Art - Santos, Telma João (2017)
Unicity and existence of bounded solutions are interesting results not just for PDE (Partial Differential Equations) but can also be extended to minimization problems in Calculus of Variations. These results also have a very interesting behavior. The reasoning and research involved in these theoretical results were part of an artistic process in performance art: the performance piece “On Self Codes”. This paper is devoted to the development of possible connections between mathematics research in Calculus of Variations and performance art through a case study. How can one construct a performance art piece inspired on specific research within mathematics, without translation and using intersubjectivities instead? How can we relate two different fields without using them hierarchically? Can we agree on affirming that this type of work is a statement regarding transdisciplinarity, or it maps the ways in which a contemporary body of work can be shaped today? Are these two features incompatible? These are some of the questions that originated this paper.